2020
DOI: 10.3389/fonc.2020.587671
|View full text |Cite
|
Sign up to set email alerts
|

Detection of ESR1 Mutations Based on Liquid Biopsy in Estrogen Receptor-Positive Metastatic Breast Cancer: Clinical Impacts and Prospects

Abstract: Endocrine therapy is the main treatment option for estrogen receptor-positive (ER+) breast cancer (BC). Compared with other clinical subtypes, ER+ BC patients usually have a more favorable prognosis. However, almost all ER+ BCpatients develop endocrine resistance and disease progression eventually. A large number of studies based on liquid biopsy suggest that ESR1 mutations may play a key role in this process. For patients with ER+ metastatic BC (MBC), ESR1 is an important prognostic factor and may associate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 104 publications
2
9
0
Order By: Relevance
“…ESR1-MUT clearly predicts poor response to single-agent AI, as previously reviewed [ 21 , 24 ] (Table 1 ). For example, the SoFEA and EFECT trials of fulvestrant versus exemestane for patients with MBC after prior progression on non-steroidal AI were retrospectively analyzed for preexisting ESR1-MUT in cfDNA [ 12 , 42 ].…”
Section: Esr1 Mutations and Aromatase Inhibitorssupporting
confidence: 53%
See 2 more Smart Citations
“…ESR1-MUT clearly predicts poor response to single-agent AI, as previously reviewed [ 21 , 24 ] (Table 1 ). For example, the SoFEA and EFECT trials of fulvestrant versus exemestane for patients with MBC after prior progression on non-steroidal AI were retrospectively analyzed for preexisting ESR1-MUT in cfDNA [ 12 , 42 ].…”
Section: Esr1 Mutations and Aromatase Inhibitorssupporting
confidence: 53%
“…There are many technologies for detecting ESR1 mutations in MBC. Sample sources include solid tissue biopsy, CTCs, and cell-free DNA (cfDNA); detection assays include next-generation sequencing (NGS) and droplet digital PCR (ddPCR), with ddPCR the most sensitive [ 21 ]. All ESR1 resistance mutations are in the LBD: the most common are D538G and Y537S; others include Y537N, Y537C, L536H, L536P, L536R, S463P, and E380Q [ 13 , 22 25 ] (Fig.…”
Section: Background and Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Several ESR1 hotspot mutations within the ligand-binding domain, including D538G and Y537S/N/C, were also detected at a lower frequency (4%). Given established treatment-associated patterns of acquired mutations in ESR1, it is not surprising that the mutation rate was not high in the setting of first-line treatment [55]. ERBB2 was the gene with the most frequent occurrence of CNVs and had an amplification rate of 22.7% (32/141) in the entire cohort and 70.5% (31/44) in the HER2 + population.…”
Section: Discussionmentioning
confidence: 99%
“…ESR1 mutations are associated with poor prognosis in ER+ MBC patients [ 37 ]. Chandarlapaty et al reported that cfDNA ESR1 mutations were associated with shorter OS of MBC patients from the BOLERO-2 study [ 10 ].…”
Section: Discussionmentioning
confidence: 99%